Resistance to deformation and fracture of 35Kh3NM steel under conditions of shock loading - Gluzman, V.D.; Kanel', G.I.; Loskutov, V.F.; Fortov, V.E. (Проблемы прочности, 1985)
Investigations of the strength properties of materials under conditions of shock-wave loading have been stimulated by the necessity of prediction of the action of intense pulsed loads on various structures. Measurements of mechanical properties under these conditions which have been described in the literature have been made primarily on low-strength materials (mild steels, aluminum alloys). In this work the strength properties and features of the α ⇆ ε structural transformation of highstrength (σt = 1.6-1.8 GPa) 35Kh3NM steel were investigated by recording of the wave profiles of the longitudinal stress σx(t) and the velocity of the free rear surface of the specimens w(t).